Three new species of Cyrtodactylus (Squamata: Gekkonidae) from Peninsular Malaysia - Grismer, L. Lee; Onn, Chan Kin; Grismer, Jesse L.; Wood, Jr., Perry L.; Belabut, Daicus (Zootaxa, 2008)
Three new species of the gekkonid genus Cyrtodactylus are described from Peninsular Malaysia; C. jarakensis sp. nov. from Pulau Jarak off the west coast of Perak, C. batucolus sp. nov. from Pulau Besar of the Water Islands Archipelago off the west coast of Melaka, and C. pantiensis sp. nov. from the Gunung Panti Forest Reserve, Johor. All are distinguishable from other Sunda Shelf species of Cyrtodactylus in having unique combinations of morphological and color pattern characteristics. The continued high potential for finding additional new species in unexplored regions of southern Peninsular Malaysia and its associated archipelagos is further supported with these findings.